Islamic-Nuanced Linear Algebra Module with Problem-Based Learning Approach for Linear Equation System Material. (February 2019) - Syazali, M; Sari, N R; Sukawati; Sari, W R; Pertiwi, S D; Putra, A; Putra, F G
Abstract: This research and development aim to determine the feasibility and attractiveness based on the students' responses toward the development of Islamic-Nuanced Linear Algebra Module with Problem-Based Learning Approach for Linear Equation System Material. This research is Research & Development model proposed by Borg & Gall that has been modified so that it only reached the 7th stage. Data collecting techniques used was a validation questionnaire sheet. The instrument used was in the form of a validation questionnaire to determine the feasibility of the product and questionnaire of students' responses to find out the attractiveness. Data analysis techniques used were quantitative descriptive and qualitative descriptive. The results of the validation obtained an average percentage score of 80.00%; 86.15%; 87.62%; 79.23%; 92.50% from the syllabus and material experts, language experts, media experts, and religious experts with the feasible and highly feasible criteria respectively. The results of the assessment on the attractiveness through the small-group trial and large-group trial were 77.50% and 79.06% with the attractive criteria. It can be concluded that the developed product is feasible and attractive.